Sprite’s Advertisement Myth Versus The Reality in Television Based on Islamic Perspective - Fitria Ayuningtyas; Witanti Prihatiningsih (Karsa: Journal of Social and Islamic Culture, 2018)
This research analyzes about Sprite’s advertisement Myth vs Reality version on television based on Islamic Perspective. The company would like to offer the freshness of the product with an extra ordinary Advertisement. This research applied the semiotic perspective from Roland Barthes to analyze connotation, denotation, myth and ideology to find the message behind the advertisement and relate this issue with Islamic perceptive. This research used qualitative approach and semiotic analysis method. The primary data was Sprite’s advertisement Myth vs Reality version. The secondary data was  literary review and other information (website) that related with the object. The analysis data of this research used semiotic model from Roland Barthes. This research analyzed all communication icons and cinematographic aspects in the Advertisement. The researcher indicated that the advertisement urges people to think logically. It urges people to understand that a drink cannot make them suddenly rich or get the ideal couple without doing nothing. Among the ways of thinking that deviate from the truth according to Islamic perspective is believe in khurafat and myth. Whereas Sprite is just a soft drink with lemon flavour.